The Influence of Instagram Social Media Promotion and Religiosity on the Decision to Stay - Alghifary, M Rasyid; Youmil Abrian (Journal of Multidimensional Management, 2025)
The rapid expansion of the global halal tourism sector, projected to reach USD 300 billion by 2026, underscores the growing demand for sharia-compliant hospitality services. This study investigates the influence of Instagram-based promotion and religiosity on guests’ decision to stay at Hotel Syariah Rangkayo Basa Padang, Indonesia. A quantitative causal–associative approach was employed, involving 150 purposively selected respondents who had prior exposure to the hotel’s Instagram promotions and had stayed at least one night. Data were collected via a structured questionnaire, validated through expert judgment and pilot testing, and analyzed using SPSS 25. Classical assumption tests confirmed normality, homoscedasticity, and absence of multicollinearity. Multiple regression analysis revealed that both Instagram-based promotion (β = 0.254, p < 0.05) and religiosity (β = 0.220, p < 0.05) significantly and positively affect guests’ decision to stay, jointly explaining 38% of its variance. These findings highlight the strategic importance of integrating visually engaging digital marketing with strong adherence to Islamic service values to enhance brand trust and meet the experiential and spiritual needs of Muslim travelers. The study contributes to halal tourism literature by bridging digital engagement strategies and religiosity-based brand positioning, offering practical insights for sharia-compliant hotel managers.